Financial Literacy and Youth Investment Decisions in a Developing Economy: Evidence from Pokhara, Nepal - Bhandari, Dipak Bahadur; GC, Deepa (Journal of Economics and Management, 2026)
In the developing countries like Nepal, financial literacy has become an important factor shaping how people make financial decisions. For young people, understanding basic financial concepts and being able to apply them in real- life situations is increasingly necessary as financial opportunities continue to expand. The study examines how different aspects of financial literacy (financial awareness, attitude, behavior and risk perception) affect the investment decisions of youth in Pokhara. The study adopts a quantitative cross-sectional research design, using data collected from 300 youths aged 18 to 40 years using a structured questionnaire. To ensure the reliability of the data, Cronbach’s alpha was used, and the results showed acceptable levels of consistency. The data were analyzed using descriptive statistics, correlation, and multiple regression techniques to better understand the relationships between the variables. The results show that financial literacy plays an important role in shaping investment decisions. However, not all components have the same level of influence. While financial attitude shows a positive connection, it doesn’t appear as a strong predictor in the regression result. In contrast, financial behavior and risk perception seem to have a more direct and meaningful impact on how young people make investment choices. The result suggests that financial knowledge is not only enough but equally important for individuals to develop good financial habits and a clear understanding of risk. Overall, the study provides important insights for policy maker, financial institution and educator who are working to improve financial literacy and better investment practices among youth in Nepal.